2022
DOI: 10.1111/myc.13512
|View full text |Cite
|
Sign up to set email alerts
|

Medium‐chain fatty acid esters are effective even in azole‐resistant Malassezia pachydermatis

Abstract: Background Malassezia (M.) pachydermatis as a frequent reason for dermatological consultation in dogs and cats was recently shown to be lipid‐dependent, too. Lipolytic activity is a prerequisite for activating antimicrobial effectivity of fatty acid esters. Objectives It was therefore of interest whether it is possible to induce this mechanism in M. pachydermatis and to identify possible differences between minimal and strong lipid‐dependent strains. Methods In an agar dilution test, the minimal inhibitory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…At the current stage, research on medium-chain fatty acid esters is limited, and they are often used as food additives (Mayser, 2015). However, recent studies have also found that this type of compound has activities such as antipsychotic and anti-bacterial activity (Koch et al, 2022). Trans-11-octadecenoic acid is a monounsaturated fatty acid that is also present in nuts and sea buckthorn fruit (Arruda et al, 2022).…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%
“…At the current stage, research on medium-chain fatty acid esters is limited, and they are often used as food additives (Mayser, 2015). However, recent studies have also found that this type of compound has activities such as antipsychotic and anti-bacterial activity (Koch et al, 2022). Trans-11-octadecenoic acid is a monounsaturated fatty acid that is also present in nuts and sea buckthorn fruit (Arruda et al, 2022).…”
Section: Molecular Dynamics Simulationmentioning
confidence: 99%